Rotor aerodynamic and noise under influence of elastic blade motion and different fuselage modeling - Yin, J.; Wall, B.G. van der; Wilke, G.A. (My University, 2014)
This paper addresses the influence of the elastic rotor blade deformation and the aerodynamic interference from the fuselage on the rotor aerodynamics as well as rotor noise characteristics. For this purpose, a BO105 Main Rotor (MR)/Tail Rotor (TR)/Fuselage configuration is chosen for the numerical simulations. An unsteady free wake 3-D panel method (UPM) is used to account non-linear effects associated with the mutual interference between MR/TR/Fuselage. DLR’s comprehensive isolated rotor code S4 and Airbus Helicopters’ (formerly: Eurocopter) rotor code HOST are coupled with UPM to account for the effect of elastic blade deformation. The effect of fuselage is simulated by using two fuselage models in UPM, (1) potential theory in form of a panelised fuselage and (2) an analytic fuselage influence formulation derived from isolated fuselage simulation based on (1). The advantage of (2) is in its computational efficiency. Finally, to evaluate either the elastic blade deformation or the impact of the fuselage on the noise radiation, the sound propagation into the far field is calculated with DLR’s FW-H code APSIM, using UPM unsteady blade loads as input. The numerical results indicate that inclusion of the MR elastic blade deformation in the simulation has clearly improved the correlation against the measured data for the three computed flight conditions. In 6° descent flight where the MR is the major source of noise, inclusion of the fuselage in the simulation has caused a reduction of MR Blade Vortex Interaction (BVI) on the advancing side. This is due to the effect of the upwash of the fuselage, which slows down the rotor downwash, slightly increases the miss distance of the tip vortex. In low speed climb and high speed level flight where the TR is the major source of noise, the inclusion of the fuselage increases slightly the TR self BVI as TR BVI on the advancing side passes over the vertical stabilizer and causes increased TR BVI noise.